Comparison of trichiasis recurrence after primary bilamellar tarsal rotation or anterior lamellar repositioning surgery performed for trachoma. (13th September 2013) - Barr, Kieran; Essex, Rohan W; Liu, Susie; Henderson, Tim
Abstract Background To compare the trichiasis recurrence rate following bilamellar tarsal rotation or anterior lamellar repositioning, performed as primary surgery for trachomatous trichiasis. Design Retrospective consecutive case series. Participants All cases of trachomatous trichiasis undergoing primary surgical correction at Alice Springs Hospital, Alice Springs, Northern Territory, Australia, between 1 June 2001 and 11 June 2011 were included. Methods Retrospective chart review. Key baseline, operative and outcome details were collected from the notes. Main Outcome Measure Recurrent trichiasis was defined as one or more lashes touching the cornea, resulting in recurrent symptoms of trichiasis and warranting further surgery in the opinion of the treating ophthalmologist. Results Sixty‐seven BTR and eighteen ALR procedures were performed, with BTR being performed from 2001 to 2008, and ALR from 2008 to 2011. The mean follow‐up times were significantly different for the BTR group (1654 days) and for the ALR group (673 days)(P < 0.001). Kaplan–Meier survival analysis did not reveal any significant differences in recurrence rate between the two procedures overall (P = 0.935). Analysis of the 2008 calendar year (the only year where both procedures were performed and therefore had equal follow‐up times) suggested that ALR might have a lower recurrence rate (1/10 ALR recurrences vs. 4/6 BTR recurrences, P = 0.181). Conclusions The results do not demonstrate a difference in the recurrence rate between the two techniques. Inconsistent follow times however leave uncertainty in this result, and a larger prospective randomised study is warranted to address this question.